CARIOGENIC MICROFLORA IN CHILDREN WITH EARLY CHILDHOOD CARIES AND THEIR MOTHERS - M Bartošová; M Kukletová; L. Izakovičová Hollá (Czech Dental Chamber, 2021)
Aim: Early childhood caries (ECC) is defined as the presence of one or more carious lesions (noncavitated or cavitated) or filled tooth surfaces in any primary tooth or missing teeth (due to caries) in children below six years of age. Cariogenic oral bacteria Streptococcus mutans, Lactobacillus spp. and Actinomyces spp. were found to be involved in the caries development. The early phase of the caries development is associated with the presence of visible plaque on the teeth surface and S. mutans occurrence in the oral cavity, with the most critical period for S. mutans colonization from 19-31 months of age. The aim of this study was to identify the cariogenic bacteria Streptococcus mutans, Lactobacillus spp., and Actinomyces spp. in children with early childhood caries and their mothers. Methods: A total of 80 mother/child pairs (child mean age 3.8 years ± 1.14 SD) were included in the study. Children were orally examined in a dental chair using a probe, mirror and a good light source. In children, the dmft index was identified, in mothers, the age, the presence of plaque, the number of caries, fillings, extracted teeth, whether they visit their dentists regularly and whether they lick their children´s spoon or pacifier were determined. The dental plaque samples for the assessment of the presence of S. mutans, Lactobacillus spp. and Actinomyces spp. were taken from the surface of carious teeth in children and surface of all teeth in mothers, always using sterile cotton swabs. The presence of cariogenic bacteria was identified by the CarioGene® test (Protean s.r.o., Dobrá voda, Czech Republic) and the results were statistically evaluated. Results: The presence of S. mutans was identified in 27 mother/child pairs, negative finding in both mother and child was found in 32 cases. The absence of Lactobacillus spp. in the children and their mothers was detected in 13 pairs, the positive finding in both in 46 cases. Actinomyces spp. was detected in both the child and mother in 67 cases. We demonstrated a significant relationship between the presence of S. mutans and Lactobacillus spp. in mothers and their children (p < 0.0001 and p < 0.00001). When mothers were split into the group who licked the spoon at feeding their and the group who did not, the results were significant only in mothers from the first group (p < 0.001). However, the results of Actinomyces spp. were not statistically significant (p > 0.05). Conclusion: The results of the study demonstrated that the source of acquiring cariogenic bacteria in children suffering from ECC might be through mothers. The potential way of transmission may be licking the infant´s spoon.